A Study on Optical Absorption Spectra of Photochromic Dye Using Mixed-Level Factorial Design - Nadir, Najiah; Wahid, Zaharah (2014)
The photochemical transformation of the organic photochromic dyes is influenced by many independent factors. One of the most important characteristics of the photochromic dyes that need to be focused on is its photostability. The effects of the type of dyes and solvents on the optical absorption spectra and fading rate constant stability have been investigated by using mixed-level factorial design. The behaviour of these dyes was observed before and after ultraviolet irradiation. From the analysis of variance results, both the type of dyes and solvents used gave significant effect on the absorbance and stability. Naphthopyran compound displayed highest change in absorbance intensity, followed by spiropyran and spirooxazine. However, spirooxazine is the most stable dye compared to naphthopyran and spiropyran.